A new species of scincid lizard in the genus Oligosoma (Reptilia: Scincidae) from the mid-Canterbury high country, New Zealand - Whitaker, Tony; Chapple, David G.; Hitchmough, Rodney A.; Lettink, Marieke; Patterson, Geoff B. (Zootaxa, 2018)
New Zealand has a diverse, endemic skink fauna, which is recognised as the most species rich skink assemblage of any cool temperate region on earth. All native New Zealand skink species are assigned to a single genus, Oligosoma Girard. A new species of Oligosoma is described from screes in montane tussock grassland in the mid-Canterbury high country, New Zealand, where it is currently known from four sites on two mountain ranges. The new species (Oligosoma hoparatea sp. nov.) can be distinguished from all congeners by a combination of mid-body scale row and lamellae counts, scale morphologies, and a bold striped pattern with smooth-edged, dark lateral bands. It is part of the O. longipes Patterson species complex, and occurs in sympatry with its closest relative, O. aff. longipes ‘southern’. The species is currently highly threatened, and is listed as Nationally Critical in New Zealand. Predation by a suite of introduced mammals is assumed to be a major threat to its survival.